2004
DOI: 10.1176/appi.ps.55.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Screening for and Detection of Depression, Panic Disorder, and PTSD in Public-Sector Obstetric Clinics

Abstract: Detection rates for depressive disorders in obstetric settings are lower than those for panic disorder and lower than those reported in other primary care settings. Consequently, a large proportion of pregnant women continue to suffer silently with depression throughout their pregnancy. Given that depressive disorders among perinatal women are highly prevalent and may have profound impact on infants and children, more work is needed to enhance detection and referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 49 publications
4
80
0
1
Order By: Relevance
“…Yet antenatal depression is equally important. In a recent US study screening for antenatal psychiatric illness, only 26% of patients who screened positive for a psychiatric illness had this illness recognised by their health care provider, only 12% of patients who showed evidence of suicidal ideation has this detected by clinicians, and only 26% of women who screened positive for major or minor depression had received or were currently receiving treatment [42].…”
Section: The Importance Of Detecting Depression In the Perinatal Periodmentioning
confidence: 98%
See 2 more Smart Citations
“…Yet antenatal depression is equally important. In a recent US study screening for antenatal psychiatric illness, only 26% of patients who screened positive for a psychiatric illness had this illness recognised by their health care provider, only 12% of patients who showed evidence of suicidal ideation has this detected by clinicians, and only 26% of women who screened positive for major or minor depression had received or were currently receiving treatment [42].…”
Section: The Importance Of Detecting Depression In the Perinatal Periodmentioning
confidence: 98%
“…Twelve studies establishing the prevalence of anxiety disorders in the perinatal period were identified (Table 7 [ 42,97,128,[206][207][208][209][210][211][212][213][214] In addition to the studies listed in Table 7, a number of studies have looked specifically at the incidence of postnatal PTSD with childbirth specified as the traumatic event [207,212,[215][216][217][218]. These studies, assessing for childbirth-specific PTSD occurring anywhere from 4 weeks to 1 year postpartum, found an incidence ranging from 0 to 6.9% with a mean of 3.8%.…”
Section: Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Women who experience IPV during or outside of pregnancy were found to have a ninefold increase in risk for mood and anxiety disorders. 20 In addition, women who experience mental health problems during pregnancy are more likely to have an adverse newborn outcome. 21 Women who are victims of IPV often do not seek health care services.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…Although a large group of women are likely to experience PD during their childbearing years, the incidence-prevalence and correlation of panic during the pregnancy period are not well defined. Limited data indicate that PD consequently affects approximately 1.5%-2.5% of pregnancies during pregnancy (10,11,12). Similarly, there are limited data on the comorbidity of PD, including Axis II disorders, during gestation.…”
Section: Introductionmentioning
confidence: 99%